Physicochemical Quality Of Cow Milk Collected From Different Sources In Adewa, Central Zone Of Tigray, Ethiopia - Tadele, Etsemeskel; Gebreananya, Brhane (Indian Journal of Dairy Science, 2024)
The study was conducted in Adewa, central zone of Tigray Ethiopia, aimed to asess the physicochemical quality of raw cow’s milk collected from smallholders, cafeterias and local vendors. A total of seventy samples of raw cow’s milk were collected and analysed. All samples were collected using proportional random sampling method. The mean values for pH, specific gravity, titratable acidity, frizzing point, TS, fat, SNF, protein, ash and lactose contents of milk samples collected from smallholders and cafeterias were 6.640±0.03, 1.032±0.04, 0.165±0.01, -0.530±0.07, 12.84±0.05, 3.98 ±0.04, 8.86 ±0.01, 3.69 ±0.03, 0.58 ±0.06, 4.58 ±0.0, 6.40 ±0.00, 1.026 ±0.00, 0.19±0.004, -0.48±0.009, 14.81±0.003, 4.63 ±0.005, 10.2±00, 4.24±0.005, 0.73±0.0013 and 5.20 ±0.002 respectively. Whereas, milk samples from Local vendors had 6.27±0.007, 1.022±0.00, 0.28±0.006, -0.49±0.001, 14.1±0.002, 4.12±0.008, 9.94±0.003, 4.41±0.003, 0.74±0.002 and 4.78±0.0028 for pH, specific gravity, titratable acidity, frizzing point, TS, fat, SNF, protein, ash and lactose content respectively. The overall mean Temperature, pH value, Specific gravity, Titratable Acidity and Freezing point samples was 26.530±0.030C, 6.440±0.03, 1.028±0.03, 0.121±0.05 and -0.515±0.00 respectively. While the TS, Fat, SNF, Protein, Salt and Lactose content were 13.67±0.05%, 4.20±0.055%, 9.46±0.04%, 4.0±0.05%, 0.66±0.07% and 4.80±0.015% respectively. The chemical quality of samples collected from cafeterias and local vendors was significantly higher (P<0.05) than small scale milk producers. The physicochemical quality of samples obtained from small scale milk producers, cafeterias and local vendors were within the standard level Except pH and titratable acidity of the samples of cafeteria’s and vendors. Therefore, this indicated that the need for improved physicochemical quality standard of milk.